Economic incidence of Mexican fiscal and labor policies - Sánchez Vela, Claudia; Valero Gil, Jorge N. (Estudios Económicos de El Colegio de México, 2013)
This paper analyzes the impact on the Mexican economy of burdens on firms, in particular those imposed by the Federal Labor Law and the Income Tax Law, whose burdens depend on the size of the firm. It is used a general equilibrium model; it starts from an equilibrium without distortions and then, burdens specified in Mexican laws are introduced. It is concluded that these taxes and evasion explain differences in firm size between Mexico and the U.S., and they do not explain the large differences in macroeconomic variables.